Digital Human Resource Management Supporting Digital Transformation: A Systematic Literature Review - Nuraini Aisiyah; Nur Wening (Maneggio, 2025)
Digital transformation has become a strategic imperative for organizations and requires human resource management (HRM) to assume a more adaptive and strategic role. This study aims to identify the main strategies, enabling factors, and challenges in implementing digital HRM to support digital transformation. A Systematic Literature Review (SLR) was conducted following PRISMA guidelines, initially identifying more than 1,000 international and national indexed articles published between 2000 and 2025. Through a structured screening and eligibility process, 23 articles were retained for in-depth analysis. The review shows that digital HRM practices including Human Resource Information Systems (HRIS), process automation, HR analytics, and digital training significantly enhance organizational efficiency, employee productivity, and competence development. Sectoral comparisons reveal different orientations: private organizations mainly emphasize productivity and competitiveness, whereas public organizations prioritize service effectiveness and accountability. The key enabling factors for successful digital HRM include transformational leadership, organizational culture readiness, and continuous development of digital skills. The findings highlight that digital transformation in HRM goes beyond technology adoption; it also requires managerial capability, change management, and cultural alignment. The study recommends cross-sector strategies and mixed-method research designs to provide a more comprehensive understanding of how digital HRM can strengthen organizational competitiveness in the digital era.